An empirical analysis of the effect of economic growth on stock market performance: a study based on Sri Lankan economy - Amaresh, M.; Anandasayanan, S. (Journal of Business Studies, 2019)
The economic growth of a country is a dominant factor in determining how prosperous a nation is. Finance is an important element of economic growth. Stock market is also playing a vital role in promoting the industry and commerce, which affects the economy of the country. Smooth functioning of a stock market will enable a country economically stabilized. Therefore the economists and financial analysts are paying more attention on the activities of stock market. The All Share Price Index is used to measure the performance of share market. The performance of stock market is being influenced by various factors, and economic growth is one of them. The sampling period of this study was from 2002 to 2018. Investigating the effect of economic growth on stock market performance by employing time series analysis is the objective of this study. The economic growth which was measured by GDP per capita was considered as independent variable and All Share Price Index (ASPI) was considered as dependent variable. Hypotheses were tested using correlation and regression analyses. The findings of regression analysis revealed that the economic growth has positive and significant impact on the performance of share market. That is, approximately 83% of the changes in the share market performance are described by the economic growth. The correlation analysis indicated that there is strong and positive correlation between economic growth and stock market performance. Economic growth plays a dominant role in accelerating the performance of stock market. The nations which have stable macro-economic environment will undergo better and increased share market performance. Appropriate economic policy amendments or abolition should be made to boost up Sri Lankan economy.
Keywords: All Share Price Index; Economic Growth; Stock Market Performance